Comparative safety and effectiveness of vedolizumab to tumour necrosis factor antagonist therapy for Crohn's disease. Issue 4 (13th July 2020) - Bohm, Matthew; Xu, Ronghui; Zhang, Yiran; Varma, Sashidhar; Fischer, Monika; Kochhar, Gursimran; Boland, Brigid; Singh, Siddharth; Hirten, Robert; Ungaro, Ryan; Shmidt, Eugenia; Lasch, Karen; et al.
Summary: Background: Direct comparisons are lacking between vedolizumab and tumour necrosis factor (TNF)‐antagonist therapy in Crohn's disease (CD). Aim: To compare safety and effectiveness of vedolizumab and TNF‐antagonist therapy in adult CD patients. Methods: Retrospective observational cohort (May 2014–December 2017) propensity score‐weighted comparison of vedolizumab vs TNF‐antagonist therapy (infliximab, adalimumab, certolizumab) in CD. Propensity scores were weighted for age, prior treatments, disease complications, extent and severity, steroid dependence, and concomitant immunosuppressive drug use. The primary outcome was comparative risk for infections or non‐infectious serious adverse events (requiring antibiotics, antivirals, antifungals, hospitalisation, or treatment discontinuation, or resulting in death). Secondary comparative effectiveness outcomes were clinical remission (resolution of CD‐related symptoms), steroid‐free clinical remission and endoscopic remission (absence of ulcers/erosions). Results: We included 1266 patients (n = 659 vedolizumab). Rates of non‐infectious serious adverse events (odds ratio [OR] 0.072, 95% confidence interval [CI] 0.012‐0.242), but not serious infections (OR 1.183, 95% CI 0.786‐1.795), were significantly lower with vedolizumab vs TNF‐antagonist therapy. Safety comparisons for non‐infectious serious adverse events remained significant after adjusting for differences in duration of exposure. No significant difference was observed between vedolizumab and TNF‐antagonist therapy for clinical remission (hazard ratio [HR] 0.932, 95% CI 0.707‐1.228), steroid‐free clinical remission (HR 1.250, 95% CI 0.677‐2.310) or endoscopic remission (HR 0.827, 95% CI 0.595‐1.151). TNF‐antagonist therapy was associated with higher treatment persistence compared with vedolizumab. Conclusions: There was a lower risk of non‐infectious serious adverse events, but not serious infections, with vedolizumab vs TNF‐antagonist therapy, with no significant difference for achieving disease remission.